Impact of Resilience on Psychological Well-Being In Breast Cancer Patients Undergoing Chemotherapy - Abd Gani Baeda; Eka Nurwahyuni (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: The most commonly used therapy for breast cancer is chemotherapy. Chemotherapy has physical and psychological side effects that affect the psychological well-being of the patient. Resilience plays an important role in changing psychological well-being. Cancer patients who have low levels of resilience will show negative psychological well-being and vice versa. However, the condition of cancer patients undergoing chemotherapy is not yet known whether resilience can change psychological well-being so that they can adapt to the stressors of chemotherapy. Purpose: This study aims to analyze the relationship between resilience and psychological well-being of breast cancer patients undergoing chemotherapy. Methods: This study was conducted using an observational analytic method with a cross-sectional approach. The population in this study were breast cancer patients who underwent chemotherapy sessions 2-6 at one of the hospitals in Malang, Indonesia. A sample of 62 people was obtained by using a stratified random sampling technique based on the chemotherapy sessions the patient underwent. Data Collection used the Connor-Davidson Resilience Scale questionnaire. Data analysis procedures were carried out in univariate and bivariate ways (lambda correlation test). Results: The Univariate analysis showed that the lowest resilience was experienced by respondents who underwent the second chemotherapy session and the bivariate analysis showed that there was a positive correlation between resilience and psychological well-being with p=0.039 and r=0.267. This means that the higher a person’s resilience, the greater the chance of having positive psychological well-being. Conclusion: This study shows that the higher the resilience, the greater the probability of experiencing positive psychological well-being. While the higher the resilience, the more likely it is to experience positive psychological well-being. It is recommended that patients who will undergo chemotherapy are given education related to therapy so that low resilience is not experienced at the beginning of chemotherapy.